Cytotoxic xanthone derivatives from the twigs of Garcinia oligantha. (June 2020) - Yang, Jinling; Fu, Wenwei; Xiang, Qian; Tang, Yuexun; Wu, Rong; Zheng, Changwu; Lu, Yue; Zhou, Hua; Xu, Hongxi
Abstract: Ten undescribed xanthone derivatives, garoliganthins A−I and oliganthaxanthone C, along with eight known compounds, were isolated from the twigs of Garcinia oligantha Merr. Their structures and absolute configurations were determined by extensive spectroscopic methods, single-crystal X-ray diffraction analysis, electronic circular dichroism analysis, and chiral HPLC/HPLC-CD analysis combined with density functional theory calculations. Garoliganthin A is an unprecedented tetrahydro-xanthone derivative possessing a bicycle [3.2.2] nonane skeleton, and garoliganthins B-E are the first examples of a new class of rearranged xanthone derivatives with six-membered lactone core scaffold. The cytotoxic effects of the isolates on four human cancer cell lines (HeLa, PC-3, A549, and K562) were measured using an MTT assay. Seven compounds showed good inhibitory activities against four cancer cell lines with IC50 values ranging from 2.1 to 16.8 μM. Graphical abstract: Ten undescribed xanthone derivatives were isolated from the twigs of Garcinia oligantha Merr. Garoliganthin A is the first representative of a novel type of tetrahydro-xanthone derivative possessing a bicycle [3.2.2] nonane skeleton. Image 1 Highlights: Ten undescribed xanthone derivatives were isolated from Garcinia oligantha. Garoliganthin A is an undescribed xanthone with bicycle [3.2.2] nonane skeleton. Garoliganthins B-E are undescribed rearranged xanthones with lactone core scaffold. Seven compounds exhibited mild to moderate cytotoxic activities.